Reconstruction Of Settlement Models Of Violence Against Women Through Development Of Restorative Justice - Abdullah, Norida; Suprobowati, Gayatri Dyah (The Mattingley Publishing Co., Inc, 2020)
The objective of this research is to explain changes in the criminal justice system in resolving violence against women by using a restorative justice model. The measure of the success of law enforcement which has so far only been marked by the conviction of a criminal, is no longer relevant to the growing age. The main thing is how law enforcement can accommodate the values of justice that develop in the community, especially for women as victims. This research is a normative study using a legal and conceptual approach. Data obtained by literature study on matters relating to the subject matter of the study. The results of the study show that cases of violence against women always increase every year. This is not balanced with ideal protection, because the criminal justice system still aims to obtain procedural justice, without regard to justice for victims. The need for restorative justice is intended so that women as victims can obtain justice because the settlement of cases is carried out through mediation, so that an agreement arises that can restore the situation of the victim